The Effect of Payo Rice Products and Prices on Consumer Repurchase Decisions - Novia, Novia; Wardi, Yunia; Idris, Idris (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
The aim of this research is to analyze the influence of Payo rice products and prices on consumer repurchase decisions. This research is quantitative research that thinks inductively, namely capturing various facts and social phenomena through observations in the field. The population of this research is consumers or people who buy Payo rice. The total sample was 150 consumers. The data analysis techniques used are descriptive analysis, analysis requirements testing and hypothesis testing with logistic regression analysis. The results of this research found that i) Product has a significant effect on the decision to repurchase Payo rice. Improved consumer perception of Payo rice will encourage consumers to repurchase Payo rice. ii) Price has a significant effect on the decision to repurchase Payo rice. The better consumer perception of the price of Payo rice will encourage consumers to repurchase Payo rice. It is hoped that from these findings, shops selling Payo rice can pay attention to the quality of Payo rice that consumers want to encourage consumer loyalty. In addition, setting prices that consumers consider appropriate will strengthen their desire to make repeat purchases. This can help rice shop owners in designing effective marketing strategies to maintain and increase the Payo rice customer base.